Summer in the city of roses - Keil, Michelle Ruiz (Soho Press, Inc., 2021)
In 1990s Portland, Oregon, seventeen-year-old Iph, aided by George, a modern-day Robin Hood, seeks her sensitive fifteen-year-old brother, Orr, while Orr has escaped wilderness boot camp and is residing with The Furies, an all-girl punk band.